Poor quality sleep is associated with greater carotid intima media thickness among otherwise healthy resident doctors - Sethi, Prativa Priyadarshani; Pathania, Monika; Gupta, Ravi; Sharma, Pankaj; Saini, Lokesh Kumar (Frontiers in Epidemiology, 2023)
Background: Sleep is important for maintaining the metabolic processes in the body, and hence, disruption in sleep leads to metabolic derangement and accelerated atherosclerosis. The effect of sleep duration on subclinical atherosclerosis has been examined in several studies; however, data regarding sleep quality is lacking. The study aimed to assess the association between sleep quality and carotid intima-media thickness among healthy young doctors. Materials and Methods: This was an observational cross-sectional study among 110 healthy young resident doctors. Anthropometric data were recorded and morning fasting venous blood samples were collected to assess fasting blood sugar, lipid profile and glycosylated haemoglobin (HbA1c). Pittsburgh Sleep Quality Index and Berlin questionnaire assessed subjective sleep quality and risk for obstructive sleep apnea, respectively. Carotid ultrasonography was done to detect the intima-media thickness. Results: Average age of the participants was 26.45 (±1.43) years, and 51.8% were male. Self-reported poor sleep quality was found in 54.5%. Carotid intima-media thickness (CIMT) was increased among 44.5% of participants. In the multivariate analysis, only poor sleep quality appeared to be associated with higher CIMT (P<0.001, OR=7.4; 95% CI= 2.70-20.32). When different components of sleep quality was analyzed through multivariate logistic regression, subjective sleep onset latency (> 30 min), sleep efficiency (<85%) and sleep disturbance was found to be associated with the increased CIMT. Conclusion: Poor sleep quality, especially prolonged sleep onset latency, poor sleep efficiency, and sleep disturbance are associated with increased carotid intima-media thickness among healthy young adults.